Pendampingan santri dalam pemanfaatan tanaman obat untuk mencegah anemia - Evi Lusiana; Muhammad Irsan Saleh; Nia Savitri Tamzil; Desi Oktariana; Tia Sabrina; Aisya Turridho; Zahrah Aliyah Qonitah (Jurnal Pengabdian Masyarakat: Humanity and Medicine, 2025)
Anemia is a condition characterized by a deficiency of hemoglobin in the blood, which can impair productivity and health, particularly among vulnerable populations such as Islamic boarding school students (santri). Education and the utilization of herbal plants have potential as effective measures for anemia prevention. However, these approaches are underutilized in this population. This study aimed to enhance the knowledge and skills of santri regarding anemia prevention, the use of herbal plants, and health screening at the Modern Thawalib Sriwijaya Islamic Boarding School in Palembang, involving 40 participants (67.5% male, 32.5% female). Activities included educational sessions, health screenings, and guidance on herbal plant cultivation. Evaluations were conducted using pretest and posttest assessments. Results demonstrated significant improvements in knowledge (from 30% to 95%), attitudes (from 15% to 65%), and practices (from 47.5% to 82.5%). Hemoglobin screening revealed moderate anemia in 42.5% of participants, mild and severe anemia in 10% each, and no anemia in 37.5% of participants. Educational interventions effectively improved the understanding, attitudes, and behaviors of santri concerning anemia and the preventive potential of herbal plants.